Spontaneous Splenic Artery Aneurysm Rupture Diagnosed at Autopsy: A Case Report - Akın, Ufuk; Aykır, Ömer Faruk; Kandemir, Ferhan (The Bulletin of Legal Medicine, 2023)
When the splenic artery reaches >1 cm in diameter, it is considered an aneurysm. The majority of splenic artery aneurysms (SAA) are asymptomatic and are usually detected incidentally on radiological imaging or autopsy. Except for splenic infarction and bleeding, fatal complications of rupture have been reported between 2% and 10%. In our study, a case in which the diagnosis of SAA rupture as the cause of death was detected at autopsy is presented. In splenic artery aneurysms, which are usually asymptomatic, complications such as rupture, which may result in high mortality, may develop. As a result, it can be encountered in emergency services with clinical pictures that require rapid intervention or in autopsies as sudden unexpected death cases. For these reasons, we think that incidental diagnoses should be kept in mind in cases requiring urgent intervention for clinicians and in postmortem examinations for forensic science experts.